Artrogripozis multipleks konjenita ve anestezi - (:unkn) unknown (My University, 1998)
Artrogripozîs multipleks konjenita nadir görülen bir sendromdur. Bu sendromda başlıca etkilenen yerler eklem ve kas dokuları olup, sıklıkla multiorgan anomalileri ve santral sinir sistemi disfonksiyonıt ile birliktedir. Bir olgu' nedeni ile artrogripozis multipleks konjenita sendromunu ve bu tür hasta-larda anestezik yaklaşımı irdelemeyi amaçladık.

Arthrogryposis multiplex congenita is a rare syndrome. Joints and muscle tissue are primarily effected in addition to multiple visceral anomalies and central nervous system dys-function. We report a case of arthrogrypo.sis multiplex con-genita and anaesthetic management in such cases is reviewed.
Arthrogryposis multiplex congenita and anaesthesia
Keywords: Genel ve Dahili Tıp